Maternal small arterial elasticity decreases with gestation in normal pregnancy. (7th June 2011) - Hogan, J L; Kennelly, M M; O'Dwyer, V; Farah, N; Turner, M J; Stuart, B
Abstract : Changes in maternal blood pressure are seen in normal pregnancy. Mean arterial pressure falls until the end of the second trimester and then rises again to prepregnancy levels in the late third trimester. The aetiology of hypertensive disease of pregnancy remains elusive but may involve changes in the arterial vessel wall. We investigated what changes in arterial elasticity occur during pregnancy. Subjects were recruited from the antenatal clinic at their first visit to the hospital. Using the HDI/ Pulsewave CR-2000 Research Cardiovascular Profiling System, we analysed the radial artery pulse pressure waveform on 660 occasions in 100 uncomplicated pregnancies between 8 and 40 weeks gestation. Reflective and capacitive arterial compliance was calculated from the pulse pressure waveform contour using a modified Windkessel model of the circulation (electrical analogue model). Centiles for artery elasticity throughout gestation were calculated and fitted using linear mixed effect modelling appropriate to longitudinal data. We found that reflective arterial compliance changes with advancing gestation. The median reflective arterial compliance is 7.6 ml/mm Hg×100 at 16 weeks gestation rising to a peak of 7.8 ml/mm Hg×100 at 20 weeks gestation and then declining to a median value of 5.8 ml/mm Hg×100 at 40 weeks gestation. We also found that capacitive artery elasticity only changes minimally with advancing gestation with a median value of 13.3 ml/mm Hg×10 at all gestations. Changes in small artery vessel wall elasticity are reciprocal to the changes in blood pressure throughout pregnancy. The increase in elasticity seen in the second trimester may contribute to the fall in mean arterial pressure. Further study is needed to clarify the aetiology of these physiological changes.